Analysis of patients’ privacy and associated factors in the perioperative period - Tan, Mingyang; Li, Hongyu; Wang, Xiaofei (Frontiers in Medicine, 2023)
Background: Healthcare professionals recognize how to protect patient privacy in order to effectively reduce the occurrence of conflict between the two parties.Therefore, understanding the protection of patient privacy during the perioperative period and the relevant factors affecting privacy is essential to improving healthcare delivery.Methods: This was a cross-sectional survey of a convenience sample of 400 perioperative patients. General demographic information, the perioperative privacy scale (PPS), and the Amsterdam preoperative anxiety and information scale (APAIS) were used for the survey. And factors affecting patient privacy were investigated by ANOVA or t-test analysis, Pearson correlation analysis, and linear regression models.Results: This study found that perioperative patient privacy satisfaction scores were (53.51±12.54). The results of the univariate analysis showed that factors affecting privacy satisfaction included gender, age, and the number of surgeries (p < 0.05).Preoperative anxiety and Information Needs Scale was negatively associated with the perioperative patient privacy satisfaction (r=-0.807, p<0.01). Further analysis was performed using linear regression models to finally obtain five factors affecting perioperative patient privacy: gender, age, anesthesia modality, the number of surgeries, and the amsterdam preoperative anxiety and information.Conclusions: Healthcare professionals working in healthcare facilities need to be aware of the sensitivity of different populations to privacy when protecting patient privacy. Patients' preoperative anxiety and information need status affect privacy satisfaction.This will mean that healthcare professionals will be able to identify key privacy concerns early and take appropriate action.